A Cross-Sectional Study of Mental Health and Wellbeing on the Bearing Transition of Students' Academic-life after COVID-19 Pandemic - Zulfitri, Zulfitri; Afna, Mauloeddin (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
The article reviewed the collective mental health and well-being of students' academic life in transition after two years of the COVID-19 outbreak. The article provided vibrant color for a cross-sectional study on mental health and well-being in academic life with COVID-19 restricted protocols of Education Teacher Training Faculty, which works on the teachers' candidates. The study employed a cross-sectional method that looped the three main students’ knowledge awareness; personal health, environment, and new-normal adaptation. Overall, 105 students participated in the COVID-19 Pandemic Mental Health Questionnaire (CoPaQ), which projected regression analysis and overviewed to identify academic-life effects. The result projected multivariate test of distractions impact which is moderately stable on 44 percent, with F on 6, 216, with p over 0.01. Also, it marked gradually latent 44 percent of personal health awareness, 68 for environment knowledge, and 68 for the new normal adaptation. In addition, MANOVA projected 68 of the bearing transition, compared to 46 of growing risk on mental health and well-being. The trends were associated with the students' essential knowledge of Covid-19 transmission and its common symptoms, obey to official policy, adapting new-normal behaviors, figuring the support of family, and religious spiritually restored. Balanced mental health and well-being will bring a bright university life and training pathways as a teacher candidate.